Wheelchair and robotic arm controls using gyro sensor - Asep Sholahuddin; Dessy Novita; Deni Setiana (Institute of Advanced Engineering and Science, 2020)
Someone who could only move his/her head and could not move his/her limbs needs a wheelchair and robotic arms which could be controlled by the head. Gyro sensor is a sensor that could be controlled according to the tilt in the x,y coordinates which then implemented to measure the tilt of the user’s head. This paper would explain the head detector application to control wheelchairs and robotic arms. They could be controlled using Arduino microcontroller which uses C programming language. Gyro sensor that is put on the head could control wheelchair to move left, right, forward and backward according to the tilt of the head. It is the same with controlling robotic arms. It could rotate left, right, and move up and down. The x and y coordinates are used to determine the tilt of the head for controlling the wheelchair as well as robotic arms’ movements. It is discovered that wheelchairs and robotic arms could be controlled by the head by the use of gyro sensor.